Faunal composition of smaller moths (microlepidoptera) in lowland tropical forest, Sarawak - Diana, anak James Junau. (Universiti Malaysia Sarawak, (UNIMAS), 2003)
A total of 222 individuals of the microlepidoptera representing 92 species were collected using an illuminated vertical light sheet from secondary lowland forest at Matang Wildlife Centre, Kota Samarahan, and Sri Arnan, Sarawak. Nine families of these smaller moths were represented, with Pyralidae as the most abundant and diverse family. The three commonest species were Cnaphalocrocis patnalis Bradley, Nacoleia charesalis Walker and Picrostomastis inductalis Walker. These were represented by 12 individuals each. Tineidae and Pterophoridae represented the least diverse families with a single species and individual collected each. The faunal composition is further discussed and compared to other available studies on moths of Borneo.